La autoestima y los problemas de conducta de los estudiantes de la Educación Básica Superior - Tircio Reyes, Adriana Lisseth (2022)
Self-esteem is an important factor that significantly influences the lives of human beings, especially adolescents in classrooms. However, teachers face various challenges such as behavior problems that students present, for this reason it is important that as educators they learn to identify the behaviors that are typical of adolescent ages and intervene with different strategies in the various subjects. The research work responds to self-esteem and its influence on behavioral problems; what has allowed to analyze this influence in the students ofthe Higher Basic Education in the Educational Unit "Academia Naval Almirante Illingworth, of the City of Guayaquil. A methodological design with a mixed approach, descriptive scope and the analytical and deductive method was carried out, in addition the interview, survey and observation sheet have been used as techniques and instruments. In this context, research shows that teachers must have the responsibility to provide not only knowledge but also to payattention to the needs of students. The proposal is based on a training program aimed at teachers to strengthen the self-esteem of students with behavioral problems in Basic Education. The results of the research proposal serve as support for the processes carried out in the institution and the direct beneficiaries will be the students, since each one will be able to overcome the difficulties in self-esteem.